Modeling Entrepreneurial Intentions among University Students: A Behavioral Finance Perspective Using PLS-SEM - Prijanto, Whinarko Juli; Sugiharti, Retno; Septiani, Yustirania (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study investigates the factors influencing entrepreneurial interest among university students, focusing on the roles of self-esteem, entrepreneurial knowledge, and self-efficacy. Using a structural modeling approach, entrepreneurial interest is analyzed as the dependent variable influenced by these psychological and cognitive constructs. A key aim of the study is to examine the mediating role of entrepreneurial knowledge between self-efficacy and entrepreneurial interest. The results reveal that both self-esteem and entrepreneurial knowledge have direct and significant effects on entrepreneurial interest. Notably, self-efficacy does not influence entrepreneurial interest directly but exerts its effect indirectly through entrepreneurial knowledge, indicating a full mediation. This finding challenges the assumption that self-belief alone is sufficient to foster entrepreneurial motivation and highlights the importance of knowledge acquisition as a cognitive pathway toward entrepreneurial engagement. The study offers practical implications for improving entrepreneurship education—particularly in developing strategies that integrate confidence-building with knowledge-focused learning.